1999
DOI: 10.1021/bi990923a
|View full text |Cite
|
Sign up to set email alerts
|

The Aromatic Residues Trp and Phe Have Different Effects on the Positioning of a Transmembrane Helix in the Microsomal Membrane

Abstract: We have examined the effect of Trp and Phe residues on the positioning of a poly-Leu transmembrane helix relative to the microsomal membrane by employing a previously described "glycosylation mapping" technique [Nilsson, I. M., Sääf, A., Whitley, P., Gafvelin, G., Waller, C., and von Heijne, G. (1998) J. Mol. Biol. 284, 1165-1175]. Both Trp and Phe tend to push the transmembrane helix into the membrane when inserted in positions flanking the poly-Leu stretch, and Trp (but not Phe) pulls the transmembrane helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
146
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 27 publications
11
146
0
Order By: Relevance
“…Perturbations primarily associated with the anisotropic chemical shifts may reflect differences in their chemical shift tensors. Perturbations in the first or last turn are likely to reflect the interaction of this helical turn with the membrane interface through amphipathic side chains, anchoring and stabilizing the TM domain in the lipid bilayer (44,45), and hence the helical backbone may be somewhat perturbed at these sites. However, it is clear that the tilt and rotational orientation of the helices remain constant throughout their lengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perturbations primarily associated with the anisotropic chemical shifts may reflect differences in their chemical shift tensors. Perturbations in the first or last turn are likely to reflect the interaction of this helical turn with the membrane interface through amphipathic side chains, anchoring and stabilizing the TM domain in the lipid bilayer (44,45), and hence the helical backbone may be somewhat perturbed at these sites. However, it is clear that the tilt and rotational orientation of the helices remain constant throughout their lengths.…”
Section: Resultsmentioning
confidence: 99%
“…These helices span nearly 30 Å of the POPC/POPG bilayer hydrophobic thickness. Two tryptophan residues at the helix termini (Trp47 on TM1 and Trp73 on TM2) have their indole N-H oriented toward the membrane interfacial regions and serve as anchors (44,57); two other tryptophans (Trp32 and Trp92) form an interhelical stacking interaction. Neighboring polar and charged residues (Ser30 and Gln52 for TM1 and Tyr75 and Arg91 for TM2) form hydrogen bonds with lipid phosphate and carbonyl groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pair of tryptophans in the pore helix is highly conserved across K þ channels. Tryptophans preferentially reside at membrane interfaces (17)(18)(19). The complex properties known as aromaticity underlie this preference (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Trp residues prefer to be positioned at a well-defined site in the lipid headgroups (3,(11)(12)(13)(14)(15) and that thereby they can act as membrane anchors. Their abundance at the lipid/water interface in several membrane proteins (5-7) is therefore likely to be functionally important, e.g.…”
mentioning
confidence: 99%